Influence of municipal management on the organization of children's healthcare in primary care services in the interior of the State of Sao Paulo, Brazil - Sanine, Patricia Rodrigues [UNESP]; Dias, Adriano [UNESP]; Machado, Dinair Ferreira [UNESP]; Tortorelli Zarili, Thais Fernanda [UNESP]; Loziglia Carrapato, Josiane Fernandes [UNESP]; Placideli, Nadia [UNESP]; Nunes, Luceime Olivia [UNESP]; Mendonca, Carolina Siqueira [UNESP]; Lodeiro Castanheira, Elen Rose [UNESP] (Cadernos Saude Publica, 2021)
The aim was to assess the association between the organizational quality of children's healthcare in primary care services and variables in the management context. An evaluative survey in 151 primary care services in 40 municipalities (counties) in the interior of the State of Sao Paulo, Brazil, answered the QualiAB in 2014 Services were scored according to 41 children's health indicators which comprised quality groups distributed by quartiles and were associated with 17 management indicators. The following were not associated with the quality groups: participation in the More Doctors Program/Provab-Medico (p = 0.102), availability of social services (p = 0.315), and high-risk pregnancy (p = (1814). The association was significant for all the others. Although for some variables, groups G1 and G2 were similar to the more polar groups (GO and G3), the latter showed differences in all the variables. The services belonging to the group considered as having the best quality (G3) were mostly organized in the Family Health Unit/Mixed model (p = 0.018), administered under outsourced management (p < 0.001), regularly supplied prenatal care (p < 0.001), had a general practitioner or family physician available on a 24/7 basis (p = 0.09), and had a support network consisting mainly of CAPSi and CAPSAd III and children's health services (p < 0.001). They also reported holding weekly team meetings (p < 0.001), studying cases of spontaneous demand (p < 0.001), and changing the management and organization of care based on the evaluative process (p = 0.004). In conclusion, organizational quality does not depend only on practices by health professionals, but also on administrators' decisions.
Keywords: Health Evaluation; Health Services; Primary Health Care; Child Health; Health Management